The view of the American intelligence services on the political activities of Alexander Kerensky in his immigration - Tokmakova Polina Dmitrievna (Studia Humanitatis, 2019)
The article considers political activity of Alexander Kerensky in emigration during his stay in the USA. The author analyses the level of Alexander Kerensky’s cooperation with the American special services and their interest in him as a political figure on the basis of the CIA archival documents. It has been suggested that Alexander Kerensky was seen as a tool in the US fight against communism with the help of the “White emigration”, but this attempt failed because of Kerensky’s political death.